Fifty Years of Generating and Advancing Knowledge: the University of Dar es Salaam ' s Experience and Outlook for the Years Ahead - Mukandala, Rwekaza S. (Papers in Education and Development, 2018)
The University of Dar es Salaam celebrated its 50th anniversary or its ' Golden Jubilee ' on 25 October 2011. The University was founded on 25 October 1961 as a University College, Dar es Salaam, in a special relationship with the University of London. Among the series of celebratory events running up to the climax, was a two-day university-level conference held on 10 and 11 October, on the theme "The University of Dar es Salaam: 50 Years of Advancing Knowledge". One of the six papers presented was based on the research-and-plan-based discussions and decisions reached in the recent past. It begins with a historical note on the foundation of the first and earliest higher institution of learning in the country, highlights the critical moments, landmarks and decisions in the 1980s €“90s period, the institutional innovations instituted or attempted, and ends with the outlook for the next fifty years, especially in the area of teaching and research, postgraduate programmes and civic engagement.